Understanding students' concepts through guided inquiry learning and free modified inquiry on static fluid material - Sularso Sularso; Widha Sunarno; Sarwanto Sarwanto (Universitas Sebelas Maret, 2017)
This study provides information on understanding students' concepts in guided inquiry learning groups and in free modified inquiry learning groups. Understanding of student concept is reviewed on the concept of static fluid case. The number of samples tested were 67 students. The sample is divided into 2 groups of students: the group is given guided inquiry learning and the group given the modified free inquiry learning. Understanding the concept of students is measured through 23 tests of items about the concept of static fluid. The result of the students 'understanding of the guide inquiry learning is better than the students' understanding of the concept of free modified inquiry learning.